TOTAL PLATE COUNT (TPC) PADA JAMUR TIRAM PUTIH SELAMA PENYIMPAN DENGAN MODIFIED ATMOSFER PACKAGING (MAP) - Ias Marroha Doli Siregar; Filli Pratama; Basuni Hamzah; Wulandari Wulandari (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2023)
White oyster mushroom (Pleurotus ostreatus) is a perishable food ingredient. The purpose of this study was to determine the total plate count in white oyster mushrooms during storage with MAP. This study consisted of two stages of the process, the first stage was sample preparation and the second stage was the analysis of the total plate count and the determination of the reaction order. The results showed that the TPC in white oyster mushrooms stored in MAP with PE plastic and the addition of 30% CO2, storage temperature of 10oC on day 0 to 10 days of storage was increase of 3.34 – 11.49 log cfu/mg. White oyster mushrooms stored for 24 hours (day 1) experienced a significant increase in TPC of 6.32 log cfu/mg. Changes in TPC of white oyster mushrooms during storage under MAP conditions at 100C tended to increase.